An Interpolation Theorem for Quasimartingales in Noncommutative Symmetric Spaces - Congbian MA; Guoxi Zhao (Advances in Mathematical Physics)
Let E be a separable symmetric space on 0,∞ and EM the corresponding noncommutative space. In this paper, we introduce a kind of quasimartingale spaces which is like but bigger than EM and obtain the following interpolation result: let E^M be the space of all bounded EM-quasimartingales and 1<p<pE<qE<q<∞. Then, there exists a symmetric space F on 0,∞ with nontrivial Boyd indices such that E^M=L^pM,L^qMF,K.